Hydrogen-oxygen therapy alleviates clinical symptoms in twelve patients hospitalized with COVID-19: A retrospective study of medical records. Issue 9 (4th March 2022) - Luo, Peng; Ding, Yuanfang; He, Yuan; Chen, Dafeng; He, Qing; Huang, Zufeng; Huang, Shian; Lei, Wei
Abstract : Abstract: A global public health crisis caused by the 2019 novel coronavirus disease (COVID-19) leads to considerable morbidity and mortality, which bring great challenge to respiratory medicine. Hydrogen-oxygen therapy contributes to treat severe respiratory diseases and improve lung functions, yet there is no information to support the clinical use of this therapy in the COVID-19 pneumonia. A retrospective study of medical records was carried out in Shishou Hospital of Traditional Chinese Medicine in Hubei, China. COVID-19 patients (aged ≥ 30 years) admitted to the hospital from January 29 to March 20, 2020 were subjected to control group (n = 12) who received routine therapy and case group (n = 12) who received additional hydrogen-oxygen therapy. The clinical characteristics of COVID-19 patients were analyzed. The physiological and biochemical indexes, including immune inflammation indicators, electrolytes, myocardial enzyme profile, and functions of liver and kidney, were examined and investigated before and after hydrogen-oxygen therapy. The results showed significant decreases in the neutrophil percentage and the concentration and abnormal proportion of C-reactive protein in COVID-19 patients received additional hydrogen-oxygen therapy. This novel therapeutic may alleviate clinical symptoms of COVID-19 patients by suppressing inflammation responses.